Mode of gene action and heterosis for physiological, biochemical, and agronomic traits in some diverse rice genotypes under normal and drought conditions - Abd-El-Aty, Mohamed S.; Abo-Youssef, Mahmoud I.; Bahgt, Mohamed M.; Ibrahim, Omar M.; Faltakh, Hana; Nouri, Hela; Korany, Shereen Magdy; Alsherif, Emad A.; AbdElgawad, Hamada; El-Tahan, Amira M. (Frontiers in Plant Science, 2023)
A study was conducted at the Experimental Farm of Rice Research and Training Center, Sakha, Kafr El-Sheikh, Egypt, during the 2017 and 2018 summer seasons. This study aimed to evaluate 31 genotypes of rice (seven lines viz., Puebla, Hispagran, IET 1444, WAB1573, Giza177, Sakha101 and Sakha105 and three testers viz., Sakha106, Sakha107 and Sakha108) and their 21 crosses produced by Line X tester mating design under normal and water deficit conditions to determine the effects of water deficit on the estimates of combining ability, heterosis and gene action for some Physiological, Biochemical and yield components traits. The results showed that water deﬁcit stress significantly decreased relative water content, total chlorophyll content, grain yield, and yield attributes. Contrarily, proline content and antioxidant enzyme activities (CAT and APX) were signiﬁcantly increased compared to well-watered conditions. Highly significant mean squares due to the genotypes and their partitions were detected for all studied traits under both conditions, except for total chlorophyll under normal irrigation. Highly significant differences were detected among lines, testers and line × tester for all the studied traits under both conditions. The value of the σ²GCA variance was less than the value of σ²SCA variance. Moreover, the ratio of σ²GCA/σ²SCA was less than unity for all studied traits. In addition, the dominance genetic variance (σ2D) was greater than the additive genetic variance (σ2A) in controlling the inheritance of all studied traits under both irrigation conditions, revealing that the non-additive gene effects played a significant role in the genetic expression of these traits. The parental genotypes Puebla and Hispagran were identiﬁed as good combiners for most Physiological and biochemical traits under study in addition to earliness, shortness, grain yield and 1000-grains weight traits under both irrigation conditions. Additionally, the cross combinations (Puebla X Sakha107), (Hispagran X Sakha108) and (Giza177 X Sakha107) were the most promising combinations which demonstrated substantial and desirable speciﬁc combining ability effects on all the tested traits, which suggested that it could be considered for use in rice hybrid breeding programs.